Pallister-Hall syndrome presenting as an intrauterine fetal demise at 39 weeks' gestation - Sunil Jaiman; Himabindu Nalluri; Nuzhat Aziz; Geeta Kolar (Wolters Kluwer Medknow Publications, 2012)
Pallister-Hall syndrome (PHS) is a pleiotropic autosomal-dominant malformation syndrome rarely presenting with genitourinary malformations. Literature has recorded 14 cases of PHS with genitourinary findings out of which only six have been females presenting with hydrometrocolpos and/or vaginal atresia. Fetal autopsy findings on a 39 weeks' gestation including demonstration of corticotroph deficiency in the pituitary, along with the review of literature is being presented here. None of the earlier literature pertaining to PHS with hydrometrocolpos and/or vaginal atresia describes an intrauterine fetal demise due to corticotroph deficiency.